Parental knowledge, attitude and practice regarding antibiotic use in children at a municipal corporation in Northeast India - Chakraborty, Kunal; Chakraborty, Ananya; Saha, Subhashish; Deb, Durba (International Journal Of Community Medicine And Public Health, 2020)
Background: Parental beliefs and expectations often lead to abuse and irrational prescriptions of antibiotics in pediatric population. The goal of this study was to examine parental knowledge, attitudes, and practices (KAP) about antibiotic use in children at the Agartala Municipal Corporation (AMC) area in northeast India. Methods: This cross- sectional study was undertaken after ethics committee approval. A questionnaire was given to parents participating in the study. The questionnaire had questions on socio-demographic profile and questions from knowledge, attitude and practice domains regarding use of antibiotics. Data was collected by house to house visit. Descriptive statistics was used to assess the knowledge and practice level and to explore the attitude about antibiotics use. Chi-square test was used to find out the determinants associated with knowledge level. Results: A total of 254 participants responded to the study. Their mean age was 31.3 (S.D; 7.8) years. Adequate knowledge about antibiotic use was found in 59.1% (150) participants. Parental age, sex, educational level, and number of children was found to be associated with the knowledge and practice of antibiotics use. 33.5% (85) respondents felt that antibiotics should be prescribed for their child whenever they suffer from cold, ear ache, throat pain. 70.9% (180) of the respondents do not give antibiotics without consulting a doctor. Conclusions: There is a trusted relationship between parents and their child’s doctors. But many parents have insufficient knowledge related to antibiotic use in children. This results in inappropriate attitudes and practices. Educational interventions will reduce inappropriate use of antibiotics.